AROMATHERAPY AS A COMPLEMENTARY APPROACH IN THE MANAGEMENT OF ANXIETY: AN INTEGRATIVE REVIEW - de Azevedo Gomes Campos, Samara; Clebia de Morais Pordeus, Liana; da Silva Falcão, Mayara; de Freitas Pacifico, Heloisa; Cristiane Xenofonte de Almeida, Sheyla (Revista Gênero e Interdisciplinaridade, 2026)
Anxiety represents a complex response of both biological and psychological nature to stimuli perceived as threatening, challenging, or capable of inducing stress. However, anxious disorders arise when this response becomes disproportionate, persisting over time and leading to detrimental consequences for the individual. In this context, Aromatherapy emerges as a complementary alternative aimed at fostering the physical, emotional, and mental well-being of individuals. Aromatherapy employs essential oils (EOs), also known as volatile oils or essences, as its main therapeutic tool. This study aimed to conduct a detailed literary analysis on Aromatherapy as an integrative and complementary approach in managing symptoms associated with anxiety. To achieve this goal, bibliographic searches were conducted in the PubMed, Scielo, CAPES Periodicals, and Virtual Health Library databases, performing a critical analysis of the studies included as research objects, respecting inclusion and exclusion criteria, as well as ethical aspects. Based on the analyzed research on aromatherapy and essential oils, inhalation administration seems to be the most common approach, with promising results in reducing anxiety and improving physical and mental well-being. The variety of application methods, such as the use of impregnated gauzes, diffusers, and personal inhalers, highlights the flexibility of aromatherapy as a complementary health intervention. Additionally, oils such as lavender, rose, and bitter orange are frequently used due to their well-known therapeutic properties. These oils, known for their calming and relaxing properties, play a significant role in the observed benefits of aromatherapy. In summary, aromatherapy emerges as a promising and complementary approach in the field of health, offering potential benefits for reducing anxiety and promoting emotional balance. Therefore, continuous research and improvement of aromatherapy protocols are essential to maximize its therapeutic effects and integrate it effectively into holistic healthcare practices.